The professionalization of schoolteachers in Spain (nineteenth and twentieth centuries): literature, biographies, memoirs - De Gabriel Fernández, Narciso (Historia y Memoria de la Educación, 2015)
The texts written by teachers and others involved in primary education serve as an important source of information for the study of the professionalization of the schoolteachers. This article analyzes a novel published in 1865, a compendium of biographies published in 1885 and the memoirs of a schoolteacher who taught during the first thirty years of the twentieth century. The texts give us insight into the profession as it was practiced by male schoolteachers and, to a lesser extent, female schoolteachers. It traces teachers’ origins, their situation and social consideration, feminization, training, pay, membership in teachers’ associations, teachers’ career paths and the relationship of teachers with local authorities. The historical period reviewed ranges from the early nineteenth century until 1936.